THE POSSIBILITIES AND CONDITIONS OF TRANSITION TO INNOVATIVE ECONOMY - N. I. Komkov (Модернизация, инновация, развитие)
The state of present Russian economics is discussed from the standpoint of conditions and problems of its transition to innovative economy. Since the time Russian economy begun transition to market relations, Russian scientific potential has suffered essential losts, its rehabilitation in XXI centuryproceeding slowly. Among numerous infrastructural, managerial and legal problems, there are those of the innovation sector «external encirclement». While solving innovative development problems, both their numerous interconnection and simultaneous implementation of the results should be taken into account.